An audit and quality assessment of the methods used to determine menstrual cycle phases in studies assessing athletic performance in elite female athletes - Sherwin, G.; Flood, T. R.; Burden, R. J.; Burke, L. M.; Field, A.; Kuikman, M. A.; McKay, A. K. A.; Smith, E. S.; Elliott-Sale, K. J. (Journal of Sports Sciences, 2026)
Menstrual cycle (MC) phases may impact athletic performance due to the non-reproductive actions of 17-ß-oestradiol and progesterone, which fluctuate across the MC. Research often includes recreational athletes, with findings generalised to elite athletes. To inform evidence-based practice and future research, the scope and quality of studies examining the relationship between athletic performance and MC phases in elite female athletes must be evaluated. This study audited these studies. Eleven studies, involving 218 athletes, were included. Of these studies, 91% (n = 198) of athletes were categorised as tier 4 (elite/international level) and 9% (n = 20) as tier 5 (world-class). The majority of studies (55%, n = 6) relied solely on calendar-based counting to delineate MC phases, while 45% (n = 5) incorporated calendar-based counting and biochemical methods. A methodological quality ranking system for MC phase determination revealed that one study achieved gold-tier status (9%); 18% achieved silver, 55% bronze, and 18% were ungraded. Research on the effects of MC phases on athletic performance in elite female athletes is of low methodological quality due to an overreliance on calendar-based counting without biochemical verification. Future research should verify MC phases to improve the research impact for elite female athletes.